The Mindset of Citizenship: How Cultural Intelligence Shapes Leader Behaviors - Zahdi, Zahdi (JURNAL AL-TANZIM, 2025)
This study examines how cultural intelligence shapes madrasah principals' leadership behaviour in Bengkulu Province in a multicultural educational context. Using a qualitative approach with a case study design, the research explores how cultural intelligence influences decision-making and social interactions in the madrasah environment. Data were collected through in-depth interviews, as well as direct observations and document analysis to ensure a comprehensive understanding of leadership practices. The findings indicate that madrasah principals with high cultural intelligence foster inclusive school environments, enhance stakeholder communication, and develop policies that respect cultural diversity. Unlike previous studies focusing on general leadership models, this research highlights integrating local cultural values as a key factor in effective leadership within religious-based schools. These insights contribute to the literature by demonstrating how cultural intelligence can be systematically applied to improve leadership practices. The study also provides a practical perspective for developing training programs emphasizing cultural adaptability and inclusive decision-making in educational institutions.